Caring for carers within the psychiatry workforce. Issue 4 (8th November 2022) - Maitra, Raka; McCowan, Sue; Cohen, Marta C
Abstract : Caring responsibilities for children and family members with complex health care needs often go unnoticed among health care staff. Statistically, a significant portion of these responsibilities are met by women, widening the gender pay gap. This article highlights the impact of caring responsibilities on physicians and the need for more inclusive work and leave policies to support recruitment and retention of this workforce, valuing both professional and lived experience in care giving.